A Concomitant Cancer Diagnosis Is Associated With Poor Cardiovascular Outcomes Among Acute Myocardial Infarction Patients - Peng, Xiang; Wang, Zhuozhong; Cao, Muhua; Zheng, Yuqi; Tian, Ya'nan; Yu, Li; Ni, Wenjun; Wang, Shanjie; Qin, Zhifeng; Zhao, Suhong; Tian, Jinwei; Yu, Bo (Frontiers in Cardiovascular Medicine, 2022)
Background and aims With the increasing coexistence of cardiovascular disease and cancer in contemporary clinical practice, studies on the outcomes in acute myocardial infarction (AMI) patients with cancer has not been systematically investigated. This study sought to investigated the effect of coexisting cancer on the treatment and clinical outcomes among AMI patients. Methods We retrospectively integrated and analyzed cardiovascular data of 6607 AMI patients between June 2016 and December 2019. Patients with cancer were compared with pair-matched cancer-naive patients. Cox proportional hazards models were constructed to compare the differences in outcomes. Results Of 6607 patients, 2.3% (n=150) had been diagnosed with cancer. Patients with cancer were older (70.3± 10.0 vs. 63.9± 11.5 years, P<0.001) and had a higher burden of comorbidities. Moreover, patients with cancer tended to receive clopidogrel (52.0% vs. 40.0%, P=0.004) rather than ticagrelor (45.6% vs. 58.2%, P=0.003) than those without cancer. After pairwise matching, patients with cancer were less likely to undergo in-hospital percutaneous coronary intervention (61.3% vs. 70.0%, P=0.055). And after 3-year follow-up, the cumulative incidence of cardiovascular death (14.0% vs. 8.3%; adjusted HR, 1.93; 95% CI, 1.11 to 3.39; P=0.021) among patients with cancer was significantly higher than that among the matched controls, a similar pattern was observed for the composite outcome of cardiovascular death, nonfatal myocardial infarction, and nonfatal stroke (16.0% vs. 10.3%; adjusted HR, 1.98; 95% CI, 1.21 to 3.26; P=0.007). Moreover, patients with a historical cancer diagnosis within 5 years had a higher risk of cardiovascular ischemic events. Conclusions AMI patients with a concomitant diagnosis of cancer tended to be treated with conservative therapies and were at substantially higher risk for adverse cardiovascular outcomes.